Slippery Surfaces: Anisotropic Slippery Surfaces: Electric‐Driven Smart Control of a Drop's Slide (Adv. Mater. 32/2016). Issue 32 (August 2016) - Guo, Tianqi; Che, Pengda; Heng, Liping; Fan, Lizhen; Jiang, Lei
Abstract : Inspired by the anisotropic sliding behavior present in pitcher plants, on page 6999 L. P. Heng, L. Z. Fan, and co‐workers present anisotropic slippery surfaces composed of directional, porous, conductive poly(3‐hexylthiophene) (P3HT) fibers and silicone oil, which exhibit excellent anisotropic sliding properties for several liquid droplets. More impressively, they successfully obtain reversible control of conductive liquid droplets sliding on these surfaces under the application of voltage.